PENGARUH KUALITAS AUDIT DAN LEVERAGE PADA AGRESIVITAS PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2017 - Putu Yudha Asteria Putri; I Gusti Ayu Ratih Permata Dewi; Putu Diah Putri Idawati (Faculty of Economics and Business, Universitas Warmadewa, 2019)
Tax aggressiveness is an action taken by the company to minimize its tax burden by conducting tax planning both legally (tax avoidance) and illegal (tax evasion). This study aims to determine the effect of audit quality and leverage on tax aggressiveness. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange in 2013-2017. The sample was chosen by the nonprobability sampling method with a purposive sampling technique. The number of observations obtained was 125 observations. The data analysis technique used is multiple linear regression. The results showed that audit quality and leverage influenced the tax aggressiveness by using the effective tax rate (ETR) proxy, cash effective tax rate (CETR), and books tax differences (BTD). Keywords: Audit quality; leverage; tax aggressiveness.